Penggunaan Model Regresi Logistic Untuk Menguji Faktor-Faktor Yang Mempengaruhi Penerimaan Going Concern Audit Opinion Pada Industru Perbankan - Astuti, Dewi Saptantinah Puji; Sarwono, Aris Eddy (STIE Surakarta, 2015)
A going concern assumption survival in an entitys financial reporting, so that if an entity has a condition that otherwise it shall become problematic. The main problems in the banking sector in Indonesia is like the crisis in 1999. The main objective of this study was to determine the main factors that affect the acceptance of a going concern audit of the banking industry in Indonesia. The data used in this research is data from the financial statements of banks in 2011 to 2013 by purposive sampling technique sampling.Technik retrieval of data using the technique documentation of the data in the IDX (Indonesia Stock Exchange), especially for the banking sector in Indonesia. Testing hypothesis in this study using multivariate analysis using logistic regression (logistic-regresion), results showed that audit tenure, the quality of audit and independent commissioners have influence on giving opinions going concern, but shopping opinion, independent directors and managerial ownership has no effect to the going concern opinion